Conserved microRNA mediates heating tolerance in germ cells versus surrounding somatic cells. Issue 10 (3rd October 2019) - Wu, Yi; Wang, Yingzheng; Liu, Qiang; Zhu, Lihua Julie; Gao, Hui; Cui, Maosheng; Liu, Jinghao; Zhao, Pengju; Liu, Jianfeng; Chen, Lei; Wang, Jinyong; Zeng, Wenxian; et al.
ABSTRACT: Mammalian fertility is reduced during heat exposure in the summer, but is regained as temperatures decrease in the autumn again. However, the mechanism underlying the phenomenon remains unknown. We investigated heat stress tolerance of germ cells and their surrounding somatic cells, and discovered that microRNA ssc-ca-1 was upregulated after heat stress in cultured porcine granulosa cells (GCs), but not in serum-starved GCs. Ssc-ca-1 inhibited heat shock protein 70 (Hsp70) expression through its 3′- and 5′-UTRs. Although Hsp70 mRNA transcription was induced in GCs by in vivo exposure to heat in the summer, ssc-ca-1 inhibited Hsp70 expression. In ovarian cultures, heat stress-induced Hsp70 expression in primordial but not in growing follicles; ssc-ca-1 expression did not change in primordial follicles, but increased in growing follicles. Consistently, ssc-ca-1 was present in testicular cells and exhibited the same function as in ovarian cells. It modulated the different Hsp70 expression between spermatogonial stem cells and Sertoli cells after scrotal heat stress. This mechanism is of relevance to mammalian fertility in parts of the world dominated by heat stress associated with global climate change.